Marine Actinobacteria as a source of compounds for phytopathogen control: An integrative metabolic-profiling / bioactivity and taxonomical approach (2017)
Marine bacteria are considered as promising sources for the discovery of novel biologically active compounds. In this study, samples of sediment, invertebrate and algae were collected from the Providencia and Santa Catalina coral reef (Colombian Caribbean Sea) with the aim of isolating Actinobateria-like strain able to produce antimicrobial and quorum quenching compounds against pathogens. Several approaches were used to select actinobacterial isolates, obtaining 203 strains from all samples. According to their 16S rRNA gene sequencing, a total of 24 strains was classified within Actinobacteria represented by three genera: Streptomyces, Micromonospora, and Gordonia. In order to assess their metabolic profiles, the actinobacterial strains were grown in liquid cultures, and LC-MS-based analyses from ethyl acetate fractions were performed. Based on taxonomical classification, screening information of activity against phytopathogenic strains and quorum quenching activity, as well as metabolic profiling, six out of the 24 isolates were selected for follow-up with chemical isolation and structure identification analyses of putative metabolites involved in antimicrobial activities.